HS-SPME as an efficient tool for discriminating chemotypes of Lippia Alba(Mill.) N. E. Brown - SILVA, Aiêrta Cristina Carrá da (Universidade Federal do Pará, 2018)
Lippia alba (Mill.) N. E. Brown (Verbenaceae) is a medicinal plant for which several biological activities are reported, such as sedative, anxiolytic, anti-ulcer, antifungal, antimicrobial, antioxidant, antispasmodic, anti-nociceptive and anti-inflammatory. It is characterized by the production of essential oils which have been used to classify the plant in different chemotypes. In the Northeast region of Brazil, the presence of three chemotypes are reported: myrcene-citral (chemotype I), limonene-citral (chemotype II) and carvone-limonene (chemotype III). In this work, headspace-solid phase microextraction (HS-SPME) was used on the analysis of the volatile organic compounds (VOCs) of three chemotypes of L. alba from the Northeast region of Brazil, and compared to the essential oils of the plants extracted by hydrodistillation. Volatile compounds from each chemotype were more effectively differentiated when extracted by HS-SPME than by hydrodistillation.